THE EXISTENCE OF THE AGGALARA’ TRADITION IN PASSUNNA’ CEREMONY IN JENEPONTO, SOUTH SULAWESI - Henri, Henri (Fakultas Ilmu Sosial dan Ilmu Politik, 2025)
This research aims to explore the existence of the aggalara’ tradition in the passunna’ ceremony, focusing on its historical background and its rhythm of implementation in the modern era in Balangloe Village, Binamu Subdistrict, Jeneponto Regency. This research employs a qualitative approach, with data collection methods including observation, interviews, and documentation. The structural theory of functionalism AGIL Talcott Parsons is used as an analytical knife to explore this research. The results reveal that the aggalara’ tradition in the passunna’ ceremony is a cultural heritage passed down from ancestors and has been practiced from ancient times to the present through generations. The aggalara’ tradition is led by a specific individual trusted by the local community, believed to be a successor mystically appointed by tau allenguk. All residents of Balangloe Village do not practice this tradition; instead, it is maintained only by a portion of the community who specifically believe that the aggalara’ tradition is an ancestral heritage that must be preserved. The advancement of modern times has also influenced the community's logic, leading to the perception that not all traditions need to be perpetuated.